Fifty key theatre directors - Mitter, Shomit; Shevtsova, Maria (London ; New York : Routledge, 2005)
Discusses each director's key productions, ideas and rehearsal methods, combining theory and practice.
Bibliografija uz pojedine radove.
Kazalo
Keywords: Theater -- Production and direction; Theatrical producers and directors -- Biography; kazališna režija; kazališni redatelji